Risiko Operasional Stasiun Pengisian dan Pengangkutan Bulk Elpiji pada PT Surya Artha Chanya - Teguh Sriwidadi; Meivi Kristiani (Binus Business Review, 2014)
PT Surya Artha Chanya is a 3kg LPG refilling service company. In charging process there are some errors and the error certainly raises the risk of loss for the company. To minimize the risk in operations, risk management is attempted. This research is a descriptive study; data collection technique used was interview with internal parties company that could be trusted. Research used Analytical Hierarchy Process method to process the data questionnaire with Expert Choice 11 software which serves to compare and find the most important indicator of the operations. To determine the amount of loss that exceeds the threshold calculation, the Generalized Pareto Distribution method was used. These methods were expected to issue the company's risk of loss can be resolved.